Effectiveness of Microecological Preparations for Improving Renal Function and Metabolic Profiles in Patients With Chronic Kidney Disease - Tan, Jiaxing; Zhou, Huan; Deng, Jiaxin; Sun, Jiantong; Zhou, Xiaoyuan; Tang, Yi; Qin, Wei (Frontiers in Nutrition, 2022)
Background Determining whether microecological preparations, including probiotics, prebiotics, and synbiotics are beneficial for patients with chronic kidney disease (CKD) has been debated. Moreover, determining which preparation has the best effect remains unclear. Here, we performed a network meta-analysis of randomized clinical trials (RCTs) to address these questions. Methods MEDLINE, EMBASE, PubMed, Web of Science, and the Cochrane Central Register of Controlled Trials were searched. Eligible RCTs with CKD patients who received intervention measures involving probiotics, prebiotics and/or synbiotics were included. The outcome indicators included changes in renal function, lipid profiles, inflammatory factors, and oxidative stress factors. Results Twenty-eight RCTs with 1373 patients were ultimately included. Probiotics showed greater effect in lowering serum creatinine (mean difference (MD) -0.21, 95% confidence interval (CI) -0.34, -0.09) and triglycerides (MD -9.98, 95% CI -19.47, -0.49) than the placebo, with the largest surface area under the cumulative ranking curve, while prebiotics and synbiotics showed no advantages. Probiotics were also able to reduce malondialdehyde (MD -0.54, 95% CI -0.96, -0.13) and increase glutathione (MD 72.86, 95% CI 25.44, 120.29). Prebiotics showed greater efficacy in decreasing high-sensitivity C-reactive protein (MD -2.06, 95% CI -3.79, -0.32) and tumor necrosis factor-α (MD -2.65, 95% CI -3.91, -1.39). Synbiotics showed a partially synergistic function in reducing malondialdehyde (MD -0.66, 95% CI -1.23, -0.09) and high-sensitivity C-reactive protein (MD -2.01, 95% CI -3.87, -0.16) and increasing total antioxidant capacity (MD 145.20, 95% CI 9.32, 281.08). Conclusion The results indicated that microbial supplements improved renal function and lipid profiles and favorably affected measures of oxidative stress and inflammation in CKD patients. After thorough consideration, probiotics provide the most comprehensive and beneficial effects for CKD patients and might be used as the best choice for microecological preparations.